Late Quaternary stratigraphic evolution of the inner continental shelf in response to sea-level change, Santa Catarina, Brazil - Cooper, J.A.G.; Meireles, R.P.; Green, A.N.; Klein, A.H.F.; Toldo, E.E. (Marine geology, 2018)
The inner continental shelf (0–50m water depth) off Santa Catarina, southern Brazil was investigated using seismic stratigraphic methods to identify and interpret the major seismic stratigraphic units and to reconstruct the late Quaternary evolution of the inner shelf and coast. The stratigraphy comprises a bedrock basement overlain by a thick (>30m) unit that comprises, in the distal portion, laminated muds and sands, and in the coast-proximal zone, offlapping deltaic deposits, whose upper surface has been reworked to form alongshore-prograding barrier spits. Deposition of this unit is tentatively attributed to sea levels (−20m MSL) during the late Pleistocene (MIS 5a, or 5c). A normal fault in the muddy units with a vertical offset of 3.5m indicates episodic tectonic activity. Cut into this unit is a profusion of incised valleys, associated with sea level fall ultimately to −120m at the last glacial maximum (LGM). The associated subaerial unconformity is only preserved close to shore, where it has escaped subsequent wave ravinement. This, coupled with the well-preserved incised valleys implies the underlying substrate to be weakly cohesive material (mud). The incised valleys display a variety of infilling sediments interpreted variously as basal fluvial sediments, estuarine basin infill muds and marginal bar or barrier-associated sands deposited during the postglacial marine transgression. During a sea level stillstand at ca. -50m, a 3.5km-wide planar surface was cut into the unconsolidated coastal plain sediments forming a terrace on which a thick sequence of sands accumulated. This unit is regionally developed and the acoustic signature implies it to comprise littoral sand including a large aeolianite component. The accumulation of sand on this mainland beach/dune system is attributed to establishment of a mature littoral system with strong longshore drift. The fact that it rests on an erosional surface that truncates incised valleys, suggests the unit to be Holocene in age. It is interpreted to have been deposited during a still stand in the Holocene and to have undergone aggradation and cementation until it was overstepped by sea-level rise. Its surface and the coastal plain to landward were then subject to wave ravinement and a thin (ca. 5–6m) layer of modern marine sands was deposited on the eroded surface. Sea-level rise continued to the regional glacio-isostatic highstand of ca. 5.5m, after which regressive strandplains developed in response to a renewed mature longshore drift system similar to that prevailing during the −50m stillstand of sea level. In the intervening period, rapid shoreline translation over the low gradient surface inhibited the development of the longshore transport system. The three shoreline systems identified show marked differences that relate to sea level change and the influence of the underlying topography. Shoreline 1 (Pleistocene highstand) developed by localised wave-reworking of delta deposits and involved a series of alongshore-prograding barrier spits on a shoreline of alternating high-relief bedrock and littoral sands in coastal re-entrants. Shoreline 2 (− 50m) was a major accumulation of beach and dune sand deposited as a mainland-attached beach dune system on a low-lying coastal plain environment. Shoreline 3 (the modern coast) comprises a series of headland-embayment beaches, strandplains and transgressive dunes with a strong bedrock control and a well-developed longshore drift system delivering sediment northward. •A seismic stratigraphy is presented for the inner shelf of Santa Catarina, Brazil.•Sea-level change and sediment supply variability have contributed to the development of temporally different depositional styles at the coast•A major shoreline deposit on the shelf is linked to development of a mature longshore drift system during a sea-level stillstand.